2016
DOI: 10.1371/journal.pone.0161011
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Independent Turnover of Human Leukocyte Antigen (HLA) Class Ia Molecules

Abstract: Major histocompatibility complex class I (MHCI) glycoproteins present cytosolic peptides to CD8+ T cells and regulate NK cell activity. Their heavy chains (HC) are expressed from up to three MHC gene loci (human leukocyte antigen [HLA]-A, -B, and -C in humans), whose extensive polymorphism maps predominantly to the antigen-binding groove, diversifying the bound peptide repertoire. Codominant expression of MHCI alleles is thus functionally critical, but how it is regulated is not fully understood. Here, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The cell surface half-life of MHC-I can be greater than 24 hours depending on the specific cell line and peptide(s) displayed [42,43]. We investigated the kinetics of MHC-I surface downregulation using a transient transfection system, finding that maximal expression of MC80 at 24 hours post transfection (hpt) did not coincide with maximal downregulation of MHC-I surface expression (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The cell surface half-life of MHC-I can be greater than 24 hours depending on the specific cell line and peptide(s) displayed [42,43]. We investigated the kinetics of MHC-I surface downregulation using a transient transfection system, finding that maximal expression of MC80 at 24 hours post transfection (hpt) did not coincide with maximal downregulation of MHC-I surface expression (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…MHC-I-peptide complexes are transported to the cell surface to enable T cell immunosurveillance of infected and neoplastic cells. Cell surface MHC-I-associated peptides (MAPs) exhibit half-lives on the order of 12 h (Blaha et al, 2019;Prevosto et al, 2016), far longer than their source polypeptides in the case of SLiPs and DRiPs (Dersh et al, 2021). Thus, MHC-I serves as a sink for peptides whose source protein translation would otherwise be invisible to MS due to their rapid degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As a specificity control, we previously reported that HLA class I molecules are not detectably rescued by PepA (or by any other protease inhibitors) in KG-1 cells (45). This suggests that CatD has no role in HLA class I degradation in this cell line, or that this enzyme acts redundantly with other lysosomal cathepsins on class I molecules.…”
Section: Fig 1 Herementioning
confidence: 93%
“…KG-1 is an acute myleloid leukemia cell line (85) with features resembling immature DCs (86,87), expressing DRB1*11 and *14 (88). Cells were grown at 37 ˚C in a humidified incubator, in RPMI1640 medium supplemented with 10% FBS, 2 mM L-glutamine, and penicillin/streptomycin, except for KG-1 cells, which were grown in IMDM with 20% Monocyte-derived dendritic cell culture Monocyte-derived dendritic cells were derived from healthy donor blood as described (45) with modifications as follows. Briefly, volunteers were recruited with ethical approval For total (surface plus intracellular) DR staining, cells were washed in PBS, fixed and permeabilized using the Cytofix/Cytoperm kit (BD), washed in 1× Perm/Wash buffer, and subsequently processed as for live staining, except that all reagents were diluted, and cells washed, in 1× Perm/Wash buffer.…”
Section: Cell Culture and Inhibitor Studiesmentioning
confidence: 99%
See 1 more Smart Citation